THE EFFECT OF COMMUNITY BASED TOTAL SANITATION WITH DIARRHEA AMONG UNDER FIVE CHIlDREN IN SAMOSIR REGENCY - Sinaga, Doni Pranciskus (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Introduction: The high rate of diarrhea Associated with hygiene and environment. Prevalence of diarrhea still high in Indonesia although program community total sanitation (STBM) has done. Proportion of diarrhea balita in Samosir regency more than 30 % in 2019.. The objective of the research was to analyze community based total sanitation with diarrhea among under five year. Methods: This was an analytic study design, based on its time used cross-sectional study design. The data was collected by observation and interviews. The sample selection was done by purposive sampling with 200 sample, which responden is the mother who have children under five year arround 3 district in Samosir regency. Data analysis using chi square test and multiple logistic regression. Result and discussion: This result showed that stop open defecation (p value 0.001), hand washing (p value 0.039), water and household food management, household waste management, and household liquid waste significantly affected diarrhea among under five year children. Conclusion: Hand washing with soap and waste disposal management more effect with diarhea, therefore its sugested for all stake holder to increase campaign of hand washing and household waste management in community.Keywords: diarrhea, children, community, hand washing, household